Utilization of Innovative Design and Production Technology to Support Coconut Milk Bonbon MSMe in Bandar Khalipah Village - Annisa FEBRIANDA; Cindy CINDY; Karin Aribi IVANKA; Nona Azzahra NASUTION; Siti AISYAH (PT Keberlanjutan Strategis Indonesia, 2025)
The Bonbon Santan Micro, Small and Medium Enterprise located in Bandar Khalipah Village, Deli Serdang Regency, is a traditional food business that has great potential to support the local economy. However, MSMEs face various challenges, ranging from limited production technology, capital, business management skills, to suboptimal marketing strategies. This community service program was implemented using a Participatory Action Research (PAR) approach to provide real solutions through training, mentoring, and the application of simple innovations. The results of this activity show an increase in production capacity after the introduction of coconut milk extractors, improved product quality that is more hygienic and consistent, and labor efficiency. In terms of marketing, distribution, which was previously limited to the village area, has been expanded to souvenir shops in Medan and several other areas such as Padang, Aceh, and Pekanbaru. In addition, the application of digital marketing through social media has also supported increased sales. This activity not only impacted business capacity but also empowered the surrounding community through involvement in production and packaging. Therefore, the sustainability of the program with capital support, advanced training, and strengthening of the distribution network is key to Bonbon Santan MSME's ability to compete regionally.